2017
DOI: 10.3390/atoms5020016
|View full text |Cite
|
Sign up to set email alerts
|

Multiconfiguration Dirac-Hartree-Fock Calculations with Spectroscopic Accuracy: Applications to Astrophysics

Abstract: Abstract:Atomic data, such as wavelengths, spectroscopic labels, broadening parameters and transition rates, are necessary for many applications, especially in plasma diagnostics, and for interpreting the spectra of distant astrophysical objects. The experiment with its limited resources is unlikely to ever be able to provide a complete dataset on any atomic system. Instead, the bulk of the data must be calculated. Based on fundamental principles and well-justified approximations, theoretical atomic physics de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 63 publications
0
31
0
Order By: Relevance
“…They have performed systematic calculations with the MCDF and MBPT methods to determine the energy levels and A-values to spectroscopic accuracy. However, for this kind of work very large calculations need to be performed for which Jönsson et al [49] have suggested further modifications to the GRASP2K code. Similarly, Safronova et al [50,51] have performed very accurate (and large) calculations for a series of ions, using the CI+MBPT codes, and with single, double and triple excitations of electrons.…”
Section: Radiative Rates and Lifetimesmentioning
confidence: 99%
“…They have performed systematic calculations with the MCDF and MBPT methods to determine the energy levels and A-values to spectroscopic accuracy. However, for this kind of work very large calculations need to be performed for which Jönsson et al [49] have suggested further modifications to the GRASP2K code. Similarly, Safronova et al [50,51] have performed very accurate (and large) calculations for a series of ions, using the CI+MBPT codes, and with single, double and triple excitations of electrons.…”
Section: Radiative Rates and Lifetimesmentioning
confidence: 99%
“…Multiconfiguration Dirac-Hartree-Fock (MCDHF) calculations with the various improvements (see e.g., [43,44]) of Ian Grant's relativistic atomic structure program GRASP are also available. Data for ions in the C, N, B, O, F, Ne, P, Si, S, Mg, Al isoelectronic sequences are now available, see [45] for a review.…”
Section: Radiative Datamentioning
confidence: 99%
“…Uncertainties in the radiative rates (oscillator strengths and A-values) can be assessed by comparing the values in the length and velocity forms [45], or more generally comparing the results of different calculations, as done e.g., for Fe XIII [74] and for N IV [75]. Other useful information is provided by laboratory measurements of radiative lifetimes.…”
Section: Uncertainties On Atomic Ratesmentioning
confidence: 99%
“…Relativistic calculations were performed using the GRASP2018 package [6]. Further details of the package can be found elsewhere [10]. Ce VIII calculations have been done parity-wise i.e., even and odd states were determined separately in the extended optimization level (EOL) scheme.…”
Section: Calculationsmentioning
confidence: 99%